Islamic Education in the Contemporary Era: Initiating a Method Format that is Enjoyable and Fun - Lutfi, Saiful; Anwar, Khairil (ALSYSTECH Journal of Education Technology, 2025)
This research aims to initiate an enjoyable and fun format of Islamic education methods as a solution in improving the effectiveness of learning in the contemporary era. The importance of this research lies in the need for innovation in learning methods that not only emphasize the transfer of religious knowledge, but also develop 21st century skills such as critical thinking, creativity, collaboration, and communication (4C). With interactive and fun learning methods, it is expected that students can be more active, enthusiastic, and have a deeper understanding of Islamic teachings. This research uses library research method by collecting and analyzing data from various relevant sources, such as books, scientific journals, and articles that discuss the concept of Joyful Learning in Islamic education. The results show that the application of the Joyful Learning method in Islamic education can increase students' learning motivation, reduce boredom in understanding religious material, and create a more conducive and interactive learning environment. Some of the strategies that can be applied in joyful Islamic learning include the use of digital technology, game-based learning, project-based learning, as well as based approach. By applying these methods, Islamic education does not only focus on the cognitive aspect, but also shapes the character of learners who are creative, communicative, and collaboration.